Mengatasi Kesulitan Membaca pada Anak Sekolah Dasar dengan Metode Belajar Interaktif - Novia Putri; Ari Suriani (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Numerous elementary students continue to face challenges in developing reading proficiency, particularly regarding text comprehension and reading fluency. These difficulties frequently stem from inadequate learning motivation and conventional teaching approaches that fail to engage students. This research aims to examine theoretically how interactive pedagogical strategies can serve as effective solutions for addressing literacy barriers in elementary education. The study employs a comprehensive literature review methodology, systematically collecting and analyzing relevant academic sources including peer-reviewed journals and educational publications. Findings indicate that interactive learning approaches, including educational gaming, collaborative small-group activities, and visual media integration, significantly enhance student engagement and reading comprehension outcomes. These methodologies foster dynamic learning environments that promote active student participation throughout the educational process. Consequently, interactive pedagogical approaches are strongly recommended as viable alternatives for effectively addressing reading difficulties among elementary school populations.